Independence of Intrapericardial Right and Left Ventricular Performance in Septic Pulmonary Hypertension - Böck, J. C.; Barker, B. C.; Lim, Aileen D.; Eichstädt, H.; Pollycove, M.; Lewis, R. F. (Nuklearmedizin - NuclearMedicine, 1990)
To study the effect of septic pulmonary hypertension on right/left ventricular intrapericardial interactions thirteen trauma patients, seven septic and six non-septic controls, were compared. Ventricular volumes were derived from firstpass or gated equilibrium radionuclide angiocardiography, and related to body surface area. Systemic and pulmonary pressures were measured invasively. Pulmonary arterial pressure was significantly increased in the sepsis group. Although right ventricular end-diastolic volumes were higher in sepsis, left ventricular end-diastolic volumes were not decreased. In terms of intrapericardial right/left ventricular interactions these results indicate that the right and left ventricles operate independently in septic pulmonary hypertension.Ziel der Studie war die Untersuchung rechts/links-ventrikulärer Interaktionen bei septischer pulmonaler Hypertension. Sieben septische und sechs nichtseptische Patienten wurden verglichen. Ventrikelvolumina wurden radionuklidangiokardiographisch gemessen. Systemische und pulmonale Drücke wurden invasiv bestimmt. In der septischen Gruppe war der pulmonalarterielle Druck signifikant erhöht. Obwohl die rechtsventrikulären enddiastolischen Volumina in der septischen Gruppe erhöht waren, waren die linksventrikulären enddiastolischen Volumina in der septischen Gruppe normal. Bezüglich der untersuchten rechts/links-ventrikulären Interaktionen zeigen diese Ergebnisse, daß der rechte und linke Ventrikel bei septischen Patienten unabhängig voneinander arbeiten.